(untitled) (Third Sector Social Economic Review, 2022)
In this study, which was carried out in order to reveal the effects of urban sprawl on the agricultural land market in the Efeler district of Aydın province, the data was collected through questionnaires from a total of 73 farmers determined by the proportional sampling used. The values of parcels which were determined by the income capitalization and the market value method were compared. Hedonic price analysis was used to determine the factors affecting the land values. The land value determined by the market value approach (38477.41 TL/da) in the examined lands was determined to be higher than the land value determined by the income capitalization approach (7174.00 TL/da). The land value calculated by the income capitalization approach remained well below the market value formed by supply and demand. The hedonic analysis results showed that the presence of the building in the parcel was the most influencing variable on the market value of the land. Since there is no legal regulation in determining the value for urban sprawl areas, there is a contradiction in the valuation process. The result of this, the land value calculated by the income capitalization approach may be below the land value calculated by the market value approach. Therefore, it is necessary to make legal regulations to determine the land value in urban sprawl areas.